2018
DOI: 10.1016/j.jvs.2017.08.091
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes at a single center after subintimal arterial flossing with antegrade-retrograde intervention for critical limb ischemia

Abstract: Retrograde pedal access is a viable revascularization technique for achieving limb salvage in patients with critical limb ischemia with acceptable patency for limb-threatening ischemia. This technique expands revascularization options after failed conventional endovascular antegrade approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The six month primary patency rate (<50% stenosis) was 78% (five studies; 95% CI 46%e99%) of 78 patients 17,19,20,22,38 the six month limb salvage rate was 77% (four studies; 95% CI 70%e84%) of 158 patients, 20,22,31,39 while major amputations were required in 20% (six studies; 95% CI 11%e32%) of 360 cases during a six month follow up. 14,17,20,25,31,35,39 Two studies enrolling 54 patients reported seven minor amputations (13%).…”
Section: Long Term Outcomesmentioning
confidence: 97%
See 2 more Smart Citations
“…The six month primary patency rate (<50% stenosis) was 78% (five studies; 95% CI 46%e99%) of 78 patients 17,19,20,22,38 the six month limb salvage rate was 77% (four studies; 95% CI 70%e84%) of 158 patients, 20,22,31,39 while major amputations were required in 20% (six studies; 95% CI 11%e32%) of 360 cases during a six month follow up. 14,17,20,25,31,35,39 Two studies enrolling 54 patients reported seven minor amputations (13%).…”
Section: Long Term Outcomesmentioning
confidence: 97%
“…3,7,12,16e 21,23e28,30,32e34,36,38,41 Five studies including 631 patients reported a 6% (95% CI 1%e15%) 30 day major amputation rate 12,16,18,23,36 and five studies investigating 764 patients with CLI demonstrated a peri-operative (within 30 days from index procedure) all cause mortality rate of 2% (95% CI 0%e5%), with most deaths attributed to MI. 14,16,18,22,39 Peri-procedural outcome details are presented in Table S4.…”
Section: Procedural and 30 Day Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, retrograde tibial or pedal access is reported to have lower technical success and primary patency rates compared with antegrade femoral access 2, 4. In some complicated CLI cases, the technical success rate was reported to be as low as 63.5%, 5 and devastating complications have been reported 3, 6. In addition, there is a steep learning curve for tibial and pedal access, and the technique subjects the operator to more radiation exposure because of proximity to the radiation source 1, 7.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 Several options have been described to address this issue, such as exploiting the subintimal space with subsequent re-entry into the true lumen. [10][11][12][13][14] In the following, we present the results from a hybrid modification of this approach. Open proximal exposure with retrograde access and stenting (OPERAS) concurrently improves inflow and provides a mechanism to directly visualize re-entry into the true lumen following retrograde subintimal crossing of a CTO.…”
Section: Introductionmentioning
confidence: 99%